Uso das Tecnologias Digitais da Informação e Comunicação no Atendimento Educacional Especializado: estudo nas Salas de Recursos Multifuncionais da rede pública municipal de São Luís - MA - CABRAL, Mozanilde Santos Nunes (2016)
This research discusses about integration of digital information and communication Technologies in the educational practices of Specialized Educational Assistance (SEA). The research sought to answer the question: How are Multifunctional Resource Rooms (MRR) teachers using digital technologies (DT) in their educational practices and what are the challenges that permeate the integration of these technologies in SEA? The main objective of this study was to investigate the practices and challenges of SEA teachers of MRR of the Municipal Public Network of São Luís - MA. Regarding the use of DT in the service of developed in the spaces. Specifically, it was intended to investigate how the uses of the digital technologies in the SEA offered in the MRR are given; Analyze the challenges faced by teachers in the use of technologies in care in these places; And to identify and to offer suggestions for continuing training for the use of DT in SEA, based on the proposals of the subjects participating in the study. The research, with a qualitative approach, adopted as means the field research, and was carried out in MRR of 15 schools of the Municipal Public Network. Data were collected through a questionnaire (25 MRR teachers) and structured interview (8 teachers, among the respondents of the questionnaire). In the analysis of the data, the content analysis was used, following the route of Bardin (2016). In view of the results obtained, it was found that the uses of DT in SEA do not occur very regularly, occur in the modality of support or support to the teaching-learning process and serve especially as a curricular and affective tool. Regarding the challenges to use, there are multiple structural barriers in MRR. In relation to the students, the difficulties are related to the lack of opportunity for the development of their abilities, those intrinsic to the Special Educational Needs (SEN), and the lack of previous knowledge about DT. Related to teachers, there is a lack of opportunity for training in the technological area and lack of mastery in the use of DT. Regarding the continuous training for the use of DT in SEA, teachers believe that these should be based on an adequate theory-practice relationship and should focus on the development of the basic skills technical and pedagogical of the technologies.